Documentary of the 2nd Global Evidence Summit: collaborating in a new era of evidence-based science - LIU Hui; SHI Qianling; LUO Xufei; WANG Zijun; QIN Yishan; WANG Bingyi; YU Xuan; CHEN Yaolong (Guangxi Yike Daxue xuebao)
From 10-13 September 2024, the 2nd Global Evidence Summit was held in Prague, the capital of the Czech Republic. The conference featured in-depth discussions on six themes: sustainable development agenda, research integrity making evidence accessible, power of synergy in evidence synthesis & synthesis products, evidence translation & implementation, advocating for greater evidence communication & use of evidence, and from global evidence to local impact. This paper aims to introduce some of the hot topics and frontier research advances in the conference to provide researchers with the latest updates in the fields of evidence-based medicine, evidence-based healthcare, medical guideline, evidence-based social science.